2008
DOI: 10.1007/s00191-008-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Growing like mushrooms? Sectoral evidence from four large European economies

Abstract: This paper follows a stream of literature on the empirics of sectoral growth rates, originated by Castaldi and Dosi (Income levels and income growth. Some new cross-country evidence and some interpretative puzzles. Our aim is to discuss the statistical properties of growth rates in light of a 'mushroom vision' of growth. In our analysis, we focus on the growth of value added in NACE five-digit sectors in France, Germany, Italy and the United Kingdom between 1995 and 2003. We find that the volatility of sectora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(6 reference statements)
1
13
0
Order By: Relevance
“…In addition, they show a much higher regularity and homogeneity than the corresponding size distributions. Accepted as a stylized fact, these distributions have been further extended to and confirmed for the growth of whole industries within a country (Sapio and Thoma 2006;Castaldi and Sapio 2008). Complementing this sectoral perspective, a logical next step is to look at the spatial intermediate level between firms and countries, namely at the level of regions.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, they show a much higher regularity and homogeneity than the corresponding size distributions. Accepted as a stylized fact, these distributions have been further extended to and confirmed for the growth of whole industries within a country (Sapio and Thoma 2006;Castaldi and Sapio 2008). Complementing this sectoral perspective, a logical next step is to look at the spatial intermediate level between firms and countries, namely at the level of regions.…”
Section: Introductionmentioning
confidence: 94%
“…However, it can be observed that even bleft and bright stay visibly below the value of a normal distribution regarding most industries with more than a hundred or hundreds of firms per region. Further investigation is needed to systematically disentangle the two effects causing the persistence of fat tails: they may emerge due to correlating mechanisms working purely at the level of regions, or firm level growth rates aggregate non-trivially: instead of compensating out in the aggregation process, they may amplify and produce extreme regional growth events (Fu et al 2005;Castaldi and Sapio 2008). tion about whether each industry has higher or lower parameter values bleft, bright, aleft and aright than the average.…”
Section: Relation Between Type Of Industry and Stochastic Characterismentioning
confidence: 99%
See 1 more Smart Citation
“…European countries display disparities related to their technological sectoral specialization, with more homogenous sectoral growth patterns evident in Germany and UK. Castaldi and Sapio (2008) conclude that the role of the diffusion of technological shocks is the key determinant in the trends of sectoral growth patterns. The results of this analysis are complemented by the results obtained in Inklaar and Timmer (2009).…”
Section: Historical Evolution Of the Eu‐us Productivity Growth Difmentioning
confidence: 87%
“…Different authors have analysed the heterogeneity in the sectoral growth patterns within the European countries. Castaldi and Sapio (2008) analyse the value added growth patterns of some sectors for a set of European countries. They follow the idea of potential convergence in the sectoral co‐evolution as a result of technological interdependencies in closer geographical areas, known as the mushroom‐like growth process and developed in Harberger (1998).…”
Section: Historical Evolution Of the Eu‐us Productivity Growth Difmentioning
confidence: 99%